2022
DOI: 10.3390/vaccines10081228
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Vaccines, Intent to Vaccinate and the Relationship with COVID-19 Vaccination Rates in Individuals with Schizophrenia

Abstract: Schizophrenia patients are at high risk of developing severe COVID-19 outcomes but recent evidence suggests that they are under-vaccinated. This study explored the role of potential attitudinal barriers by comparing schizophrenia patients with participants from the general population regarding COVID-19 vaccination rates, general attitudes towards vaccines, and willingness to take a COVID-19 vaccine. We conducted a cross-sectional study between April 2021 and October 2021. A total of 100 people with schizophren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…The observed mediation is noteworthy in that it shows that confidence in one’s vaccination decision is influenced by attitudes toward vaccination, which, in turn, is influenced by IU. This demonstrates the importance of attitudes towards vaccination in the decision to get vaccinated and to recommend or have one’s relatives vaccinated, as previously demonstrated [ 28 ], while showing a link with two other variables of interest (IU and confidence in one’s decision). However, it should be noted that an individual’s decision made in a context in which they decide on the basis of given information should be distinguished from individuals’ attitudes towards vaccination and their level of IU, both of which are inherent to the individual and independent of the context.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The observed mediation is noteworthy in that it shows that confidence in one’s vaccination decision is influenced by attitudes toward vaccination, which, in turn, is influenced by IU. This demonstrates the importance of attitudes towards vaccination in the decision to get vaccinated and to recommend or have one’s relatives vaccinated, as previously demonstrated [ 28 ], while showing a link with two other variables of interest (IU and confidence in one’s decision). However, it should be noted that an individual’s decision made in a context in which they decide on the basis of given information should be distinguished from individuals’ attitudes towards vaccination and their level of IU, both of which are inherent to the individual and independent of the context.…”
Section: Discussionsupporting
confidence: 75%
“…The COVID-19 case illustrates that pandemic contexts are particularly conducive to the study of the impact of uncertainty on decision-making. This type of situation also makes it possible to study decision-making in relation to traits of interest, such as attitude towards vaccines, which, in the case of COVID-19, reduced the probability of people with negative attitudes towards vaccines being vaccinated [ 28 ], or IU, as previously stated (especially as the lack of studies linking IU and COVID-19 has already been identified [ 4 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-one of the 33 reviewed studies identified patients with mental health conditions through clinical diagnoses obtained from medical records (Bai et al, 2021; Cai et al, 2022; Curtis, Inglesby, MacKenna, et al, 2022; Curtis, Inglesby, Morton, et al, 2022; Eyllon et al, 2022; Gibbon et al, 2021; Hassan et al, 2022; Jefsen et al, 2021; Mazereel et al, 2021; Moeller et al, 2021; Nilsson et al, 2022; Nishimi, Neylan, et al, 2022; Qin et al, 2022; Raffard et al, 2022; Ren et al, 2021; Shkalim Zemer et al, 2022; Sullivan et al, 2022; Tsai et al, 2022; Tzur Bitan et al, 2022; Uvais, 2022; L. Wang et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen of the 33 reviewed studies reported on the association between mental health conditions and the uptake of the COVID-19 vaccine or booster vaccine (Table 2, Balut et al, 2021; Curtis, Inglesby, MacKenna, et al, 2022; Curtis, Inglesby, Morton, et al, 2022; Gibbon et al, 2021; Hassan et al, 2022; Huang et al, 2021; Mazereel et al, 2021; Moeller et al, 2021; Murphy et al, 2022; Nguyen et al, 2022; Nilsson et al, 2022; Qin et al, 2022; Raffard et al, 2022; Sekizawa et al, 2022; Shkalim Zemer et al, 2022; Tzur Bitan et al, 2022; Uvais, 2022). Sizes of the studies ranged from N=62 to 57.9 million.…”
Section: Resultsmentioning
confidence: 99%
“…Unwillingness to vaccine has been associated with greater psychiatric symptoms in patients with schizophrenia: symptomatic patients with schizophrenia frequently are suspicious of the Government for wanting to vaccinate people and develop paranoid delusions around the vaccination itself and the process [55][56][57]. However, this suspicion was not limited to patients with psychotic disorders and younger age, lower education and economic status, right-wing and conservative ideology have been associated with increased belief in misinformation [58].…”
Section: Vaccination Policies Unwillingness To Vaccine and Rates Of V...mentioning
confidence: 99%